2015
DOI: 10.2135/cropsci2014.09.0634
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity for Russian Wheat Aphid Resistance as Determined by Genome‐Wide Association Mapping and Inheritance in Progeny

Abstract: Russian wheat aphid (RWA) [Diuraphis noxia (Mordvilko)] is an increasing problem on barley (Hordeum vulgare L.) throughout the world. Genetic resistance has been identified and used to create barley germplasm and cultivars adapted to the United States. Several mapping studies have been conducted to identify loci associated with resistance, but questions remain, particularly regarding the extent of genetic diversity among resistance sources and improved lines and cultivars. Association analysis of resistant (R)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 26 publications
(62 reference statements)
0
10
0
Order By: Relevance
“…The ISSR marker for resistance QTL1 on chromosome 2H was less precise in the Barke than in the Lina genetic background when validated in BC 2 F 1 DH lines, probably due to it being located less distally, at 13.1 cM (Cheung et al 2010 ), than the SNP markers from the present study at 0–6 cM. Barley chromosomes 2H and 3H may harbor QTL for resistance to RWA and GB as well, but their locations differ from those conferring resistance to R. padi (Nieto-Lopez and Blake 1994 ; Mittal et al 2008 ; Cheung et al 2010 ; Tocho et al 2012 , 2013 ; Azhaguvel et al 2014 ; Dahleen et al 2015 ).…”
Section: Discussionmentioning
confidence: 55%
“…The ISSR marker for resistance QTL1 on chromosome 2H was less precise in the Barke than in the Lina genetic background when validated in BC 2 F 1 DH lines, probably due to it being located less distally, at 13.1 cM (Cheung et al 2010 ), than the SNP markers from the present study at 0–6 cM. Barley chromosomes 2H and 3H may harbor QTL for resistance to RWA and GB as well, but their locations differ from those conferring resistance to R. padi (Nieto-Lopez and Blake 1994 ; Mittal et al 2008 ; Cheung et al 2010 ; Tocho et al 2012 , 2013 ; Azhaguvel et al 2014 ; Dahleen et al 2015 ).…”
Section: Discussionmentioning
confidence: 55%
“…The RWA resistance loci on 2H is at 27 and 39 cM (Mittal et al 2008;Mittal et al 2009, respectively), 18 and 20 cM (Dahleen et al 2015), 70-96 cM (Tocho et al 2012) and at 70-96 cM for GB resistance as well (Tocho et al 2013) and thus not at the same locus as the present QTL for R. padi resistance. The RWA resistance locus on 3H is at around 147 and 108 cM (Mittal et al 2008(Mittal et al , 2009 and 136 cM (Dahleen et al 2015), potentially within the region of the gramine QTL in our study. Resistance to GB was also located in that region of 3H, at ca.…”
Section: Discussionmentioning
confidence: 69%
“…QTL analyses and genome-wide association mapping of RWA resistance in barley have revealed several responsible loci; among them loci on chromosome 2H and 3H (Nieto-Lopez and Blake 1994;Mittal et al 2008Mittal et al , 2009Tocho et al 2012Tocho et al , 2013Dahleen et al 2015). The RWA resistance loci on 2H is at 27 and 39 cM (Mittal et al 2008;Mittal et al 2009, respectively), 18 and 20 cM (Dahleen et al 2015), 70-96 cM (Tocho et al 2012) and at 70-96 cM for GB resistance as well (Tocho et al 2013) and thus not at the same locus as the present QTL for R. padi resistance. The RWA resistance locus on 3H is at around 147 and 108 cM (Mittal et al 2008(Mittal et al , 2009 and 136 cM (Dahleen et al 2015), potentially within the region of the gramine QTL in our study.…”
Section: Discussionmentioning
confidence: 80%
“…After Diuraphis noxia Kurdjumov (Hemiptera: Aphididae) was detected in the western USA in (Stoetzel, 1987), it rapidly became a major pest of wheat and barley (Brooks et al, 1994), causing over $1 billion in damage and control costs in the first decade after it was found here (Morrison and Peairs, 1998). Wheat varieties resistant to D. noxia began to be used in 1996, and research has revealed multiple genes affecting resistance to D. noxia in wheat (Fazel-Najafabadi et al, 2015) and barley (Dahleen et al, 2015). However, aphid genotypes able to overcome one or more of these resistance genes began appearing by 2003 (Haley et al, 2004), and four virulent biotypes of D. noxia have been discovered, some of which have become widespread (Puterka et al, 2015;Randolph et al, 2009).…”
Section: Introductionmentioning
confidence: 99%